Little Bigfoot, big city - Weiner, Jennifer (Weiner, Jennifer. Littlest Bigfoot novel, 2017)
After discovering that she is not human, twelve-year-old Alice Mayfair is on a mission to find out who and what she is, but she must do it alone because her best friend Millie Maximus, an undersized Bigfoot who lives in the forest near Alice's school in upstate New York, is focused on fulfilling her dream to sing for a nationally televised talent competition.